Civil War Spain Versus Swedish Harmony: The Quality of Government Factor. (September 2014) - Lapuente, Victor; Rothstein, Bo
In 1936, while Sweden gave birth to one of the most peaceful solutions to class conflict (i.e., the neo-corporatist welfare state), Spain gave birth to one of the most violent outcomes of class conflict: the Spanish Civil War. Why did the political and socio-economic elites choose collaboration in Sweden and violent confrontation in Spain? This article underlines an overlooked intervening factor: the organization of the bureaucracy. In the late 19th century, semi-authoritarian Sweden created a meritocratic autonomous bureaucracy. In contrast, Spain—where executive and administrative positions were frequently accountable to parliamentary dynamics—built a patronage-based administration. The result was that the ruling Swedish Left could not offer public offices to core supporters and had to restrict its policies to satisfy the (more collaborationist) demands of its "policy-seekers, " while the ruling Spanish Left, thanks to the ample margin of maneuver it enjoyed to appoint and promote state officials, could satisfy the (more confrontational) demands of its "office-seekers."